Severity of diastolic dysfunction predicts myocardial infarction - Tanmay A. Gokhale; Mehak Dhande; Suresh Mulukutla; Oscar C. Marroquin; Floyd Thoma; Aditya Bhonsale; Krishna Kancharla; Andrew Voigt; Alaa A. Shalaby; N.A. Mark Estes, III; Sandeep K. Jain; Samir Saba (International Journal of Cardiology: Heart & Vasculature)
Background: Diastolic dysfunction (DD) is known to be a predictor of mortality. However, the impact of DD on the risk for myocardial infarction (MI) is not well defined. We sought to examine whether DD is an independent predictor of risk of MI in patients with a preserved ejection fraction. Methods: This was an observational study of consecutive patients who underwent an echocardiogram that showed normal systolic function and had ≥ 3 months of follow-up. DD was graded using the contemporaneous guidelines at the time of the echocardiogram. Subsequent MI was determined by an inpatient encounter with a primary diagnosis of MI. Results: 129,476 patients were included (mean age 56 years; 58 % women). DD was present in 17.6 % of patients (13.6 % Grade I, 3.6 % Grade II, 0.4 % Grade III). Patients with DD were more likely to be older and have cardiovascular comorbidities. Survival free from MI was significantly lower as DD severity increased. Multivariate Cox proportional hazards modeling demonstrated that DD was an independent predictor of MI (hazard ratios [CI]: Grade I: 1.48 [1.33–1.66]; Grade II: 1.84 [1.57–2.16]; Grade III: 2.90 [1.98–4.25]). Conclusion: Our data demonstrate that the risk of MI is significantly increased in the presence of DD, with higher risk at higher grades of DD. The increased risk associated with grade III DD is comparable to that from a prior history of percutaneous coronary intervention. These findings suggest that the severity of DD may be a useful tool in stratifying patients for risk of MI.